The impact of preoperative atrial fibrillation on survival and outcomes in heartmate II and heartmate 3 patients - Rami Al-khusein; Alish Kolashov; Nikolaus Marx; Ajay Moza; Ahmad Abugameh; Yousif Ibrahim Mohamed; Assila Al-Ahmed; Mohammed Shoaib; Leyla Dogan; Rashad Zayat; Mohammad Amen Khattab (BMC Cardiovascular Disorders)
Abstract Background Atrial fibrillation (AF) is prevalent among patients with left ventricular assist devices (LVADs); however, the exact influence of different types of AF on the clinical outcomes of these patients is unknown. The purpose of this study was to ascertain the impact of different types of AF on the outcomes of patients with LVADs. Methods The records of 162 patients with the LVADs HeartMate 3 (n = 64) and HeartMate II (n = 98) at a single center were reviewed. Kaplan‒Meier survival analysis and Cox proportional hazards regression were used to analyze the associations among paroxysmal atrial fibrillation (pAF), permanent atrial fibrillation (peAF), survival, hemorrhage, and thromboembolism. To adjust for confounding factors, we also used the inverse probability of treatment weighting (IPTW) method and estimated the average treatment effect (ATE) for the outcomes of ischemic stroke (IS), mortality and right heart failure (RHF). Clinical trial number: not applicable. Results Of the 56 (34.6%) patients with preoperative AF, 38 patients had pAF and 18 patients had peAF. Overall survival differed significantly among the three groups (log-rank test: p = 0.001). Patients with peAF or pAF had a greater incidence of postoperative right heart failure (RHF) than did patients with sinus arrhythmia (SR) (p = 0.037). According to the univariate and multivariate Cox regression analyses, both pAF and peAF were independent risk factors for post-LVAD IS (hazard ratio [HR]: 3.65 (95% CI: 1.28–10.41, p = 0.016 and HR: 9.48 (2.94–30.56), p < 0.001). Patients with preoperative peAF or pAF who received an LVAD did not have an increased risk for hemorrhagic stroke. After IPTW, the ATE with respect to mortality was significantly different between patients with peAF and those with SR (p < 0.001). The ATE with respect to post-LVAD IS was significantly different for the pAF vs. SR and the peAF vs. SR patient groups (p = 0.035 and p = 0.004). After IPTW, the ATE for the RHF outcome did not significantly differ among the three groups. Conclusions Patients with preoperative pAF or peAF who underwent LVAD implantation had a higher risk of IS than patients with SR. Our data demonstrated that only preoperative peAF is associated with poor survival while SR is not.